2020
DOI: 10.1002/maco.202011530
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synovial fluid temperature on the corrosion resistance of Ti6Al4V, Ti6Al7Nb, and CoCrMo alloys

Abstract: The frictional heat generated during the operation of the joint prosthesis in vivo could change the corrosion resistance of the prosthesis material. In this paper, the corrosion behavior of three medical alloys at different synovial fluid temperatures was analyzed using electrochemical measurement technology. Furthermore, the scanning electron microscope and energy‐dispersive spectrometer were used to characterize the surface morphology and composition of the alloys after long‐term immersion. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A positive correlation has been reported between the radius of the capacitive reactance arc in the Nyquist diagram and the R ct value of the investigated electrode. 27 Figure 6B shows that all specimens had similar arc shapes, suggesting that the corrosion mechanism was similar, while the SLM and CNC groups exhibited a larger arc than the CAST group. With the method of fitting, the R ct values in descending order were SLM (250.06 ±37.40 kU•cm 2 ), CNC (128.70 ±32.26 kU•cm 2 ), and CAST (54.70 ±14.60 kU•cm 2 ).…”
Section: Discussionmentioning
confidence: 91%
“…A positive correlation has been reported between the radius of the capacitive reactance arc in the Nyquist diagram and the R ct value of the investigated electrode. 27 Figure 6B shows that all specimens had similar arc shapes, suggesting that the corrosion mechanism was similar, while the SLM and CNC groups exhibited a larger arc than the CAST group. With the method of fitting, the R ct values in descending order were SLM (250.06 ±37.40 kU•cm 2 ), CNC (128.70 ±32.26 kU•cm 2 ), and CAST (54.70 ±14.60 kU•cm 2 ).…”
Section: Discussionmentioning
confidence: 91%
“…Research has demonstrated that in vivo service of hip prostheses results in higher frictional heat generation at the contact interface compared to natural joints. [33][34][35][36] The temperature rise has a considerable impact on the oxidative behavior of the polymer materials. 37,38 Usually, plastic deformation and severe adhesion of UHMWPE will occur above 50 C. With the increase of temperatures, hardness and wear resistance of UHMWPE register a marked reduction, and the wear resistance diminishes faster than the hardness.…”
Section: Temperaturementioning
confidence: 99%
“…Research has demonstrated that in vivo service of hip prostheses results in higher frictional heat generation at the contact interface compared to natural joints 33–36 . The temperature rise has a considerable impact on the oxidative behavior of the polymer materials 37,38 .…”
Section: The Main Influencing Factors Affecting the Oxidation Behavio...mentioning
confidence: 99%
“…281 and 84 μm/yr, respectively. This can be explained by the higher passivation ability of the Ti-6Al-4V, leading to the formation of a protective oxide layer at the surface of the sample [55][56][57]. Zirconium, as a transition metal, presents also a passivation behavior [58,59] and protects the substrates thanks to a lower OCP.…”
Section: Potentiodynamic Polarization Curvesmentioning
confidence: 99%